The link between tax, trade and investment: Tensions and opportunities - Jeffrey Owens; Ruth Wamuyu (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2025)
Reactions to global tax reforms highlight ongoing tensions between national tax sovereignty and obligations under tax, trade, and investment agreements. Despite these issues, investment competition will persist, requiring countries to adopt multifaceted strategies that recognize the interconnectedness and synergies among tax, trade, and investment disciplines.
Keywords: 330